Bladder-emptying methods, neurogenic lower urinary tract dysfunction and impact on quality of life in people with long-term spinal cord injury. (2nd January 2017) - Adriaansen, Jacinthe J. E.; van Asbeck, Floris W. A.; Tepper, Marga; Faber, Willemijn X.; Visser-Meily, Johanna M. A.; de Kort, Laetitia M. O.; Post, Marcel W. M.
Abstract : Objectives : To describe bladder-emptying methods used by people with long-term spinal cord injury (SCI) and to determine usage differences in relation to time since injury, sex, lesion level and completeness of lesion. Furthermore, to evaluate the relationship between bladder-emptying methods and the impact of neurogenic lower urinary tract dysfunction (NLUTD) on quality of life (QoL). Design : Cross-sectional multicenter study. Setting : Dutch community. Participants : Persons dependent on wheelchairs ( N  = 282) with traumatic or non-traumatic SCI for ≥10 years and age at injury of 18–35 years. Interventions : Not applicable. Outcome measures : The International Lower Urinary Tract Function Basic SCI Data Set and the Short-Form Qualiveen (SF-Qualiveen). Results : Median time since injury was 22.0 years (IQR: 16.8–30.3). Clean intermittent catheterization (CIC) was most commonly used (42.6%). Longer time since injury was associated with fewer continent urinary diversions and more transurethral catheter use. Transurethral catheter use and continent urinary diversions were more prevalent among women. Participants with tetraplegia were more likely to use reflex voiding or a suprapubic catheter, and participants with paraplegia were more likely to use CIC. Transurethral catheter users reported the highest impact of NLUTD on quality of life (SF-Qualiveen score: 1.9; SD = 0.8). Participants with a continent urinary diversion reported the lowest impact (SF-Qualiveen score: 0.9; SD = 0.6). Higher age and indwelling catheter use versus CIC were associated with a higher impact of NLUTD on QoL. Conclusions : CIC is the most common bladder-emptying method in Dutch people with long-term SCI. Clinicians should be aware of the impact of NLUTD on QoL, especially for those using an indwelling catheter.